Meler-Fock transformations in problems of wave diffraction on unclosed structures in the time region - Doroshenko, V. A.; Kravchenko, V. F.; Pustovoit, V. I. (IEEE, 2005)
In the present paper, we propose and substantiate a novel method for solving boundary value problems for the wave equation in wedge-like and conic regions.
Keywords: Meler-Fock transformations; diffraction